2020
DOI: 10.3390/molecules25061470
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk and Risk of Resistance Selection Due to Antimicrobials’ Occurrence in Two Polish Wastewater Treatment Plants and Receiving Surface Water

Abstract: In this study, a screening of 26 selected antimicrobials using liquid chromatography coupled to a tandem mass spectrometry method in two Polish wastewater treatment plants and their receiving surface waters was provided. The highest average concentrations of metronidazole (7400 ng/L), ciprofloxacin (4300 ng/L), vancomycin (3200 ng/L), and sulfamethoxazole (3000 ng/L) were observed in influent of WWTP2. Ciprofloxacin and sulfamethoxazole were the most dominant antimicrobials in influent and effluent of both WWT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…[ 52 , 53 , 54 , 55 , 56 ]. Human activities (wastewater treatment, agriculture, tourism) also contribute to the spread of MDR enterococci and VRE both in and outside the hospital environment around the world [ 14 , 35 , 36 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 52 , 53 , 54 , 55 , 56 ]. Human activities (wastewater treatment, agriculture, tourism) also contribute to the spread of MDR enterococci and VRE both in and outside the hospital environment around the world [ 14 , 35 , 36 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results clearly indicate that antibiotic-resistant enterococci are transferred to rivers with TWW. Numerous studies have demonstrated that the percentage of MDR enterococci and other bacterial groups continues to increase in TWW evacuated to water bodies [ 33 , 36 , 37 , 41 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disinfectants are crucial for sterilization but they may also be selecting for resistant strains and therefore contributing to the rise of resistant microbes [ 45 ]. A commonly overlooked cause of AMR is the discharging of pharmaceutically active compounds (PhACs) effluent into the environment from the production of raw materials used to make antibiotics [ 46 ]. Yet the contemporary governance on water quality majorly targets the presence of index microorganisms but does not focus on the antimicrobial concentrations in sewage, the influents, and effluents of wastewater treatment plants.…”
Section: Resultsmentioning
confidence: 99%
“…Seven research articles deal with the presence of pharmaceuticals in wastewater samples and evaluate their fate, ecotoxicity and/or elimination in wastewater treatment plants (WWTPs) equipped with different purification technologies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
mentioning
confidence: 99%
“…Giebułtowicz et al [ 1 ] have provided a comprehensive overview of the presence of 26 selected antibiotics in two Polish WWTPs (wastewater and sludge) and have provided crucial information on their removal efficiency and their risk to resistance selection as well as cyanobacteria and eukaryotic species. They established that the removal efficiency of these compounds was more than 50% for both WWTPs.…”
mentioning
confidence: 99%